(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Data on 8 new to Ukraine species of lichenicolous fungi Dacampia cladoniicola Halıcı & A.Ö. Türk, Dactylospora rimulicola (Müll. Arg.) Hafellner, Didymellopsis latitans (Nyl.) Clem. & Shear, D. pulposi (Zopf) Grube & Hafellner, Lichenoconium pyxidatae (Oudem.) Petrak et H. Sydow, Polycoccum teresum Halici et K. Knudsen, Zwaсkhiomyces diederichii D. Hawksw. & Ittur., Z. dispersus (J. Lahm et Körb.) Triebel et Grube are provided.